Determination of the Young's modulus of porous ß-type Ti-40Nb by finite element analysis - Zhuravleva, K.; Mueller, R.; Schultz, Ludwig; Eckert, Jurgen; Gebert, Annett; Bobeth, Manfred; Cuniberti, Gianaurelio (Giovanni) (Materials and Design, 2014)
Macroporous ß-type Ti-40Nb compacts with particularly low stiffness suitable for biomedical applications were successfully processed by a space-holder sintering method with a total porosity range of 50-60%. The microstructure of these samples as well as their phase composition and their mechanical properties were carefully analyzed. The samples comprise macropores with 100-300. μm size formed by NaCl space-holder particles and micropores of 1-3. μm size within the sintered Ti-Nb alloy. The correlation between the mesoscopic Young's modulus and the microporosity of the alloy was analyzed by combining compression tests, microcomputer tomography (μCT), and finite element analysis (FE). The derived relationship permits to predict the macroscopic Young's modulus of macroporous compacts for a known morphology of the macroporosity.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Biomaterials; Finite element analysis; Porous materials; Titanium alloys